Предмет: Алгебра,
автор: kkoroleva1
5x-2 дробь 4 -2x-4 дробь 3 =х+3 дробь 6
Ответы
Автор ответа:
0
(5х-2)/4 - (2х-4)/3 = (х+3)/6
3*(5х-2)-4*(2х-4)=2*(х+3)
15х-6-8х+16=2х+6
15х-8х-2х=6+6-16
5х=-4
х=-4/5
х=-0,8
3*(5х-2)-4*(2х-4)=2*(х+3)
15х-6-8х+16=2х+6
15х-8х-2х=6+6-16
5х=-4
х=-4/5
х=-0,8
Похожие вопросы
Предмет: Алгебра,
автор: polevmaksim99
Предмет: История,
автор: mawapilipenko2003
Предмет: Математика,
автор: glazunovandrey2006
Предмет: История,
автор: Venus12
Предмет: Обществознание,
автор: meowdasha2000